Reversal learning is influenced by cognitive flexibility and develops throughout early adolescence - Christoph Bamberg; Sarah Weigelt; Klara Hagelweide (npj Science of Learning)
Abstract Learning behavioural responses and adapting them based on feedback is crucial from a young age, continuing to develop into young adulthood. This study examines the development trajectory and contributing factors from childhood to adulthood using a reversal learning paradigm. We tested 202 participants aged 10 to 22 in an online study, where they learned and reversed stimulus-outcome associations in a new blocked design paradigm and were assessed for working memory capacity. Results showed that reversal learning performance improved with age, particularly for 10- to 14-year-olds. Flexible responses to negative feedback correlated with better reversal learning. Additionally, pubertal development and working memory were positively associated with reversal learning. These findings align with previous research, highlighting flexible feedback responses as a key factor in reversal learning. As the overall rate of flexible reactions did not change with age, it could support reversal learning independent of age, potentially changing its role during development.